Factores que influyen en la desintegración de las familias atendidas en la asociación nuevos pasos del distrito de Laredo en el año 2015. - Avalos Calle, Cinthia Karla (2016)
Research thesis entitled "FACTORS AFFECTING THE DECAY OF FAMILIES SERVED IN ASSOCIATION NEW STEPS DISTRICT OF LAREDO IN THE YEAR 2015", arose from the need to understand what are the circumstances that contribute to a family disintegrates in terms of structure and functionality as the study population are single-parent families and large type where mothers are the ones who learned the economic costs according to food, education, clothing, etc. This research aims to identify how family factors influencing characterized by problems of violence, alcoholism and breach of parental roles in the disintegration of families; likewise know how social factors of migration and crime influence the disintegration of families, and finally determine how they influence economic factors characterized by unemployment and low income in the disintegration of families. The methods used were the inductive method - deductive, ethnographic and statistical. And according to the techniques they were observation, unstructured interview, survey, informal conversations and literature review; Likewise instruments as a record of interview, social profile and questionnaires according to the variables of violence, alcoholism and parental roles. The sample universe consisted of 26 families belonging to the Residential Care Center New Steps and Child Eater New Steps Association Laredo District; the results confirm that the factors that have influenced the disintegration of the family are: alcoholism, which in most cases parents have alcohol dependence, leading it to another factor that also influences the disintegration as is in this case the physical and psychological violence by the same to the mother of his children. Social and economic factors also influence the disintegration of families such as emigration and low income.